2020
DOI: 10.1039/d0sc03059g
|View full text |Cite
|
Sign up to set email alerts
|

Stereoretention in styrene heterodimerisation promoted by one-electron oxidants

Abstract: Radical cations generated from the oxidation of C=C p-bonds are synthetically useful reactive intermediates for C–C and C–X bond formation. Radical cation formation, induced by sub-stoichiometric amounts of external oxidant,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 117 publications
0
9
0
Order By: Relevance
“…The authors later extended their method to the construction of highly functionalized cyclobutanes with complementary all- trans and trans – cis – trans relative stereochemistry via PIDA-catalyzed intramolecular dimerization of silicon-tethered alkenes and bis-allylethers in HFIP . The influence of the cis - and trans -configuration of the alkene on the stereochemical outcome of the transformation was investigated computationally . Additional exploration of the reaction mechanism focused on the initially proposed bimolecular single-electron reduction of the hypervalent iodine reagent, which was unfavored.…”
Section: Hypervalent Iodine Chemistrymentioning
confidence: 99%
“…The authors later extended their method to the construction of highly functionalized cyclobutanes with complementary all- trans and trans – cis – trans relative stereochemistry via PIDA-catalyzed intramolecular dimerization of silicon-tethered alkenes and bis-allylethers in HFIP . The influence of the cis - and trans -configuration of the alkene on the stereochemical outcome of the transformation was investigated computationally . Additional exploration of the reaction mechanism focused on the initially proposed bimolecular single-electron reduction of the hypervalent iodine reagent, which was unfavored.…”
Section: Hypervalent Iodine Chemistrymentioning
confidence: 99%
“…All calculations were carried out at the MN15/def2-TZVPPD/SMD//MN15/6-31+G­(d,p)+SDD­(Au)/SMD level of theory, with implicit solvation . Paton’s parameters were used to manually define HFIP using the SMD model . The def2-TZVPPD basis set was obtained from the Basis Set Exchange .…”
Section: Resultsmentioning
confidence: 99%
“…87 Paton's parameters were used to manually define HFIP using the SMD model. 88 The def2-TZVPPD basis set was obtained from the Basis Set Exchange. 89 Energies quoted are free energies relative to [AuCl(IPr)] (1) and include a +1.89 kcal/mol correction to reflect a 1 mol/L rather than 1 atm state.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, we herein interpret DFT simulations on the HOMD and HETD that gives all‐ trans cyclobutane under HVIRs with PIDA and DMP , respectively, featuring (1) the nature of initiation whether one or two‐electron reduction with considerations involved the effect of HFIP on the reactivity of this protocol, and (2) realizing the dynamical nature of homo‐ and heterodimerization via quasiclassical trajectory molecular dynamics (QCTMD) simulations. [ 51b ]…”
Section: Introductionmentioning
confidence: 99%
“…A recent computational study reported by Zhan and Paton has evaluated the stereoretention in the styrene heterodimerization promoted by a single‐electron oxidant. [ 51a ] However, the nature of initiation in the dimerization was incomplete. Therefore, we herein interpret DFT simulations on the HOMD and HETD that gives all‐ trans cyclobutane under HVIRs with PIDA and DMP , respectively, featuring (1) the nature of initiation whether one or two‐electron reduction with considerations involved the effect of HFIP on the reactivity of this protocol, and (2) realizing the dynamical nature of homo‐ and heterodimerization via quasiclassical trajectory molecular dynamics (QCTMD) simulations.…”
Section: Introductionmentioning
confidence: 99%